Small and medium industry export development strategy - Etty Puji Lestari; Rossanto Dwi Handoyo; Kabiru Hannafi Ibrahim; Tri Kurniawati Retnaningsih; Elok Lita Pradinda; Tamat Sarmidi; Yessi Rahmawati; Deni Kusumawardani; Tri Haryanto; Angga Erlando (Cogent Business & Management, 2024)
The small and medium industries are key to improving national and global economies and yet the industries are faced with many challenges in accessing global markets, building global networks and cooperation, and accessing technology. To this end, this study aims to analyze the export development strategy of small and medium industries in Indonesia. The study applied an Analytic Hierarchy Process (AHP) by formulating it based on priority factor weights condition, competition, demand condition, and associated supporting industry. In the study, primary data were sourced by giving questionnaires to exporters in small and medium industries, government agencies, academics, trade experts, importers, and Indonesian trade representatives. The empirical strategy revealed that the priority weight of the small and medium industry export development factor was the demand condition factor with a consistency index of 0.007 showing consistent results as it falls below the 0.1 threshold index. The results of the priority weighting of the small and medium industry export development strategy are the development of a marketplace with the results of a consistency index analysis with a value of 0.05 which shows consistent results because the consistency index value is below 0.1. The study further recommends that the government needs to conduct more in-depth research on the nature of consumers at home and abroad. Innovating products by following market developments will help producers attract more consumers. Governments can play an important role in increasing the level of quality and complexity of a country's comparative advantage.
Keywords: 650; analytic hierarchy process; super decision; small and medium industry; indonesia